Evaluation of an innovative sheep cheese with antioxidant activity enriched with different thyme essential oil lecithin liposomes. (15th January 2022) - Gil, Katarzyna Angelika; Jerković, Igor; Marijanović, Zvonimir; Manca, Maria Letizia; Caddeo, Carla; Tuberoso, Carlo Ignazio Giovanni
Abstract: The aim of this study was to develop an innovative sheep cheese enriched with Thymus capitatus L. essential oil (EO) nanoincorporated into small homogeneous liposomes. The latter were prepared using two types of lecithin: one commonly used for liposome production, and the other used as dietary supplement. Both EO liposomes, which showed similar physico-chemical characteristics (i.e., size, homogeneity, surface charge), were incorporated into fresh sheep cheese. These enriched sheep cheeses were produced in Sardinia (Italy) and analysed 20, 60 and 180 days after preparation. HS-SPME at 40 and 80 °C coupled with GC-MS/FID method was used to evaluate the volatile fraction and identify the main compounds of both EO and cheese. A validated HPLC-DAD analysis allowed the identification and quantification of thymol and carvacrol, and thymol amount dosed at 20 days was the highest (9.51–10.10 mg/kg). The amount of monoterpenoid phenols and the antiradical and total antioxidant capacity evaluated by FRAP and DPPH assays, decreased linearly ( r ≥ 0.93, p ≤ 0.05) as the cheese maturation increased. Overall results suggested that sheep cheese enriched with T. capitatus EO nanoformulations had an enhanced antioxidant activity compared to cheese without liposomal EO, up to 180 days. Highlights: An innovative enriched sheep cheese was developed. Thymus capitatus L. essential oil was nanoincorporated in liposomes. Thymol amount in cheese at 180 days ranged between 2.53 and 3.53 mg/kg. Antiradical and total antioxidant capacities were enhanced until 180 days.